Role of Community Based Organizations (CBOs) in Providing Health Care Services: A Case Study of Baloch Women Domestic Workers (Journal of Asian Development Studies, 2024)
This qualitative study delves into the complex dynamics of healthcare community-based organizations (CBOs) supporting Baloch women domestic workers in Garden West, Karachi City. The research aims to assess CBOs' efficiency in improving healthcare access, identify challenges these organizations face, evaluate their impact on Baloch women's health outcomes, and understand women's perceptions of CBO services. Semi-structured interviews were conducted with CBO heads, healthcare workers, and Baloch women domestic workers. Thematic analysis of the data reveals economic challenges faced by Baloch women, barriers to healthcare access, and the crucial role CBOs play in addressing these issues. Findings further advocate for dismantling barriers, fostering inclusivity, and amplifying voices often overlooked. The study advocates for tailored interventions to address economic and healthcare challenges, emphasizing the importance of context-specific solutions for sustainable community well-being.